CHARACTERIZATION PHYSICAL AND CHEMICAL OF SESAME SEED OIL (Sesamum indicum L.) METHYL ESTER AND COMPOSITION - Aji Zaldya NMC; Daniel Daniel; Irfan Ashari Hiyahara; Agustina R Magdaleni (JURNAL KIMIA MULAWARMAN, 2023)
The methyl ester of sesame seed oil (Sesame seeds L.) was used to make diethanolamide. This process involvedextraction, transesterification, and amidation. The research revealed that extraction by maceration yielded a sesame seed oil yield of 36.14 percent, an acid number of 1.1531 mg KOH/g, a FFA number of 0.5796 percent, and a saponification number of 51.287 mg KOH/g. In the process of converting sesame seed oil to methyl ester, the acid number was 0.5126 mg KOH/g, the FFA number decreased to 0.2704%, and the saponification number was 50.049 mg KOH/g. According to methyl ester GC-MS analysis, methyl oleate made up 39.13% of the methyl ester of sesame seed oil. The methyl ester FT-IR spectrum exhibits a specific absorption peak at 1743 cm-1 for C=O ester.